2017
DOI: 10.1097/md.0000000000008238
|View full text |Cite
|
Sign up to set email alerts
|

The hypospadias classification affected the surgical outcomes of staged oral mucosa graft urethroplasty in hypospadias reoperation

Abstract: The staged graft urethroplasty is a recommended technique for repairing complex hypospadias. This retrospective study aimed to investigate the outcomes of this technique in hypospadias patients undergoing reoperation and to analyze the underlying contributing factors including age, meatus location, and graft and suture type.We retrospectively analyzed 40 hypospadias patients undergoing reoperation who received a staged oral graft urethroplasty, including 15 buccal mucosal grafts and 25 lingual mucosal grafts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Our outcomes are similar to those in the existing literature with Snodgrass et al Faure et al [14] and Badawy H et al [10] by 38%,38.4% and 43.2% respectively, which was considerably higher than that reported by Bracka [7], Manasherova d et al [8] and Zheng D et al [20] by 23.5%,28% and 33% respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our outcomes are similar to those in the existing literature with Snodgrass et al Faure et al [14] and Badawy H et al [10] by 38%,38.4% and 43.2% respectively, which was considerably higher than that reported by Bracka [7], Manasherova d et al [8] and Zheng D et al [20] by 23.5%,28% and 33% respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, urethra-cutaneous fistula was seen in 18.2% with preputial graft group and 23.8% in buccal graft group, which was comparable to the reported rate of fistula in grafted two stage technique. Zheng et al [20], Manasherova D et al [8] and Badawy H et al [10] have reported 20.5%, 20% and 21.6% fistula rate in their respective studies with Bracka-staged repair using preputial graft.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dhua and the association reported that TVF had an optimal tissue coverage of the neourethra than the DF (3 fistulae in the DF group) (3). In contrast, Zheng et al reported similar fistula rates of DF and TVF (27). A systematic review recommended a double DF for distal hypospadias and TVF for proximal hypospadias during TIP surgery (28).…”
Section: Discussionmentioning
confidence: 96%
“…Hypospadias is a common congenital malformation of male reproductive system. The incidence rate of hypospadias is about 0.3% ( Barbagli et al, 2017 , Zheng et al, 2017 , Horiguchi, 2017 , Nelson et al, 2005 , Li et al, 2003 , Baskin, 2008 , Sugarman et al, 2015 ). The main clinical manifestations are chordee, dorsal prepuce covering the glans penis and abnormal urethral external orifice located at any position of the ventral side of the penis.…”
Section: Introductionmentioning
confidence: 99%